Nomographs for Polymeric Material Selection for Environmental Conscious Design of Industrial Products - Pandey, Vidya Shanker; Agrawal, Anil Kumar; Dubey, Ashish (My University, 2023)
Environmentally-conscious product design using Life Cycle Assessment (LCA) deserves the utmost attention to save and sustain our planet’s lives, flora and fauna. The choice of materials during the design stage needs to address environmental concerns from their sourcing to production and ultimately going up to the disposal stage. A good majority of industrial products are still not designed, focusing the environmental concerns. The inclusion and practice of the LCA approach during product designing are in a nascent stage not only in India but even over the rest of the world. Nowadays, polymers share a major chunk of the volume of goods produced worldwide and thus have a significant effect on the environment. The available design books or nomographs guide the selection of materials considering several criteria but not considering the related environmental issues. This paper attempts to bridge this gap only for the selection of polymeric materials by providing some easily interpretable and visually ready reckoners in the form of 3-D nomographs. These 3-D nomographs, graphical representations developed using the Solidworks software, echo the material’s Environmental Impact (EI) potential on an axis with some two material properties (e.g., tensile strength and density) on the other two axes. 3-D nomographs are suitably transformed into 2-D nomographs without the loss of any information. EIs on these nomographs were computed using SimaPro software. The potential EI of any product and the overall environmental burden due to them can be significantly reduced, and more so when they are mass-produced, by selecting the right materials using these nomographs. Such an approach will help in fulfilling long-term sustainable development goals of society and the globe.
This paper published affiliation with IIT (BHU), Varanasi in open access mode.
Keywords: Material selection; Nomographs; Polymers; Product design